2020
DOI: 10.7554/elife.57920
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages promote endothelial-to-mesenchymal transition via MT1-MMP/TGFβ1 after myocardial infarction

Abstract: Macrophages (Mφs) produce factors that participate in cardiac repair and remodeling after myocardial infarction (MI); however, how these factors crosstalk with other cell types mediating repair is not fully understood. Here, we demonstrated that cardiac Mφs increased expression of Mmp14 (MT1-MMP) 7 days post-MI. We selectively inactivated the Mmp14 gene in Mφs using a genetic strategy (Mmp14f/f:Lyz2-Cre). This conditional KO (MAC-Mmp14 KO) resulted in attenuated post-MI cardiac dysfunction, reduced fibrosis, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 71 publications
1
35
0
Order By: Relevance
“…TAM-associated genes enrolled in this study were broadly reported as follows: The pan-macrophage marker CD68 is now generally utilized to identify TAMs in pathological specimen and has been reported associated with controversial prognostic value in patients with cancers including breast and ovarian cancer ( Wang et al, 2018 ); CD163 as well as CD206 tend to be associated with worse clinical outcome and have been defined as M2-related markers combined with myeloid marker CD11b in most researches ( Lu-Emerson et al, 2013 ; Xu et al, 2020 ); Cytokines and chemokines, including IL-10, TGFB1, CXCL8, and CCL17, play the immunosuppressive roles in the TME via recruiting regulatory T cells and myeloid-derived suppressor cells, serving as functional biomarker of TAMs ( Cassetta and Pollard, 2018 ; Yang et al, 2019a ); Metabolic enzymes, such as ARG1, IDO1, and ENTPD1, play key roles in regulating immune balance via various metabolic signaling pathways ( Takenaka et al, 2019 ; Vitale et al, 2019 ); MMP14, a matrix metalloproteinase, has also been reported to induce TAM immunosuppression and could predict the prognosis of cancers ( Alonso-Herranz et al, 2020 ); CD274, also known as PD-L1, contributing to the well-known PD-1/PD-L1 immune checkpoint theory, was involved in TAM immunosuppression ( Noguchi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…TAM-associated genes enrolled in this study were broadly reported as follows: The pan-macrophage marker CD68 is now generally utilized to identify TAMs in pathological specimen and has been reported associated with controversial prognostic value in patients with cancers including breast and ovarian cancer ( Wang et al, 2018 ); CD163 as well as CD206 tend to be associated with worse clinical outcome and have been defined as M2-related markers combined with myeloid marker CD11b in most researches ( Lu-Emerson et al, 2013 ; Xu et al, 2020 ); Cytokines and chemokines, including IL-10, TGFB1, CXCL8, and CCL17, play the immunosuppressive roles in the TME via recruiting regulatory T cells and myeloid-derived suppressor cells, serving as functional biomarker of TAMs ( Cassetta and Pollard, 2018 ; Yang et al, 2019a ); Metabolic enzymes, such as ARG1, IDO1, and ENTPD1, play key roles in regulating immune balance via various metabolic signaling pathways ( Takenaka et al, 2019 ; Vitale et al, 2019 ); MMP14, a matrix metalloproteinase, has also been reported to induce TAM immunosuppression and could predict the prognosis of cancers ( Alonso-Herranz et al, 2020 ); CD274, also known as PD-L1, contributing to the well-known PD-1/PD-L1 immune checkpoint theory, was involved in TAM immunosuppression ( Noguchi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages play important roles in removing necrotic cellular debris, and damaged ECM from the tissues and recruiting other immune cells through the secretion of pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), IL-1β, and IL-6, which further sustain inflammation. In the MI model induced by ischemic injury using permanent ligation of the left anterior descending coronary artery, macrophages that produce such pro-inflammatory cytokines have been shown to contribute to cardiac dysfunction after MI through EndoMT [ 12 ]. The expression of matrix metalloproteinase (MMP) 14 was upregulated after MI.…”
Section: Inflammation-mediated Endomtmentioning
confidence: 99%
“…The conversion of endothelial cells into fibroblasts during the EndMT was originally described in the context of experimental wound repair [27]. Endothelial cells have also been reported to contribute to fibroblast production and aggregation in fibrotic diseases of the lung, heart, eye, kidney and other organs [28][29][30][31]. The EndMT is characterised by the loss of intercellular junctions between endothelial cells, which acquire an invasive and migratory phenotype and exhibit upregulated expression of mesenchymal cell markers such as alpha-smooth muscle actin (α-SMA), fibroblast-specific protein-1 and vimentin.…”
Section: Introductionmentioning
confidence: 99%